INTEGRATIVE COMPETENCE OF FUTURE SPECIALISTS: PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF FORMATION IN HIGHER EDUCATION INSTITUTIONS - SINISHINA Viktoriіa; SAVITSKA Viktoriіa (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The article outlines the relevance of psychological and pedagogical aspects of the formation of integrative competence of future professionals in higher education institutions. It is substantiated that in modern conditions integrativeness as a principle of development of society, science, production, education, which provides interdisciplinary complexity, generalization, the density of knowledge, methods and means of cognition, as well as a new development in educational structures, necessitates the formation of integrative competence. Within the article, integrative competence is considered from the standpoint of psychophysiological, activity, personal, personal-functional approaches. The article aims to determine the content and features of the formation of integrative competence based on the analysis of psychological and pedagogical aspects of the process of training future professionals in higher education institutions. The psychological and pedagogical aspects of the formation of integrative competence of future specialists are determined, the implementation of which should be carried out in the following areas: functional-target, problem-cognitive, procedural-methodical and integrative-effective. It is substantiated that the formation of integrative competence of future specialists is facilitated by the use of some types of project activities of students (simulation-professional game projects, information-analytical projects, specialized practice-oriented projects), as well as the use of multifunctional integrated portfolio, case sets, contextual educational technologies, individual multifunctional integrative case set off a specialist. It is generalized that the implementation of the selected psychological and pedagogical aspects of the formation of integrative competence of future professionals scientifically and methodologically provides interdisciplinary links, content and logical unity of different special disciplines; the relationship between theoretical training courses and various workshops, types of industrial practice and quasi-professional activities. Further research is identified in the development of forms of interaction between the university and employers to improve the professional and practical competence of future professionals; development of a self-educational culture of students in the process of mastering the technology of professional activity; training of teachers of higher education institutions to work on the formation of integrative competence of future specialists in various fields of training.